Tropical forests and the genus Homo. Issue 6 (November 2016) - Roberts, Patrick; Boivin, Nicole; Lee‐Thorp, Julia; Petraglia, Michael; Stock, Jay
Abstract : Tropical forests constitute some of the most diverse and complex terrestrial ecosystems on the planet. From the Miocene onward, they have acted as a backdrop to the ongoing evolution of our closest living relatives, the great apes, and provided the cradle for the emergence of early hominins, who retained arboreal physiological adaptations at least into the Late Pliocene. There also now exists growing evidence, from the Late Pleistocene onward, for tool‐assisted intensification of tropical forest occupation and resource extraction by our own species, Homo sapiens . However, between the Late Pliocene and Late Pleistocene there is an apparent gap in clear and convincing evidence for the use of tropical forests by hominins, including early members of our own genus. In discussions of Late Pliocene and Early Pleistocene hominin evolution, including the emergence and later expansion of Homo species across the globe, tropical forest adaptations tend to be eclipsed by open, savanna environments. Thus far, it is not clear whether this Early‐Middle Pleistocene lacuna in Homo ‐rainforest interaction is real and representative of an adaptive shift with the emergence of our species or if it is simply reflective of preservation bias.